PENINGKATAN HASIL BELAJAR MATEMATIKA PADA SOAL CERITA MELALUI STRATEGI THINK TALK WRITE (TTW) SISWA KELAS V SD NEGERI 02 GEMANTAR - Kamulyan, Mulyadi Sri; Ermawati, Santi (Universitas Muhammadiyah Surakarta, 2014)
Classroom action research is one of the efforts of teachers in teaching skills upgradingand simultaneously improve the ability to manage learning in the classroom. In mathematicslearning has become one of the subject is regarded as the benchmark performanceof other maple, require attention before another subject. Therefore, this research isalso about “the increase in the Mathematics learning outcomes through the story aboutlearning strategies Think Talk Write (TTW). This type of research is the PTK (ClassroomAction Research. Subject receiver is action Elementary School fifth grade students 02Gemantar totaling 22 students. Data were collected using observations at the beginningof the study remedy find problems in class, documentation to record the traces of mathematicslearning outcome , a test to determine the achievement of learning outcomesafter a given action . Data analysis was performed with data reduction step, the presentationof the data, drawing conclusions and verification. This study was conducted in severalcycles, the final study showed an increase in learning outcomes in mathematics storyproblems with strategies Think Talk Write. It can be seen from the results obtained studyingpre cycle 7 students reach KKM with an average 52.727, and 31.819 % mastery learning.In the first cycle obtained by 12 students who achieve KKM with the average value of71.59%, and mastery learning 54.55 %. In the second cycle obtained by 19 students reachKKM with an average value of 81.25%, and 86.364 % mastery learning. The results ofthis study can be concluded that the implementation of strategies Think Talk Write (TTW)can improve learning outcomes in math word problems .